PENGARUH PENCAMPURAN DAN RASIO PREKURSOR/DOPAN DALAM PEMBUATAN LAPISAN TIPIS FLUORINE DOPED TIN OXIDE (FTO) BERBASIS TIMAH (II) KLORIDA[The Effect of Mixing Condition and Dopant/Precursor Ratio in Fabrication of Fluorine Doped Tin Oxide (FTO) Thin Film Based on Tin (II) Chloride] - Latifa Hanum Lalasari (National Research and Innovation Agency (BRIN), 2015)
Flourine-doped tin oxide (FTO) merupakan salah satu oksida yang umum digunakan dalam pelapisan pada kaca yang diberi perlakuan tertentu agar dapat menghantarkan listrik. FTO ini diharapkan dapat menggantikan fungsi indium tin oxide (ITO) yang bahan bakunya sangat mahal dan tersedia dalam jumlah yang terbatas. Percobaan pendahuluan tentang pembuatan lapisan tipis F-SnO2 dilakukan menggunakan kombinasi metode sol gel dan dip coating. Percobaan ini menggunakan bahan baku timah (II) klorida hidrat (SnCl2.2H2O) sebagai prekursor dan ammonium florida (NH4F) sebagai doping. Hasil percobaan menunjukkan bahwa lamanya waktu pencampuran antar prekursor dan doping tidak begitu mempengaruhi kestabilan larutan. Faktor yang signifikan mempengaruhi adalah kondisi pencampuran antara prekursor dan doping. yang terkontrol. Lapisan tipis SnO2 yang dihasilkan dalam percobaan ini mempunyai morfologi heksagonal tidak teratur dan fasa Sn4OF6. AbstractFluorine-doped tin oxide (FTO) is an oxide that is commonly used in the coating on the glass treated aparticular treatment in order to be able to conduct electricity. FTO is expected to replace indium tin oxide(ITO) whose raw materials are very expensive and available in limited quantities. Preliminary experimentson the manufacture of F-SnO2 thin film done with using combinations of sol gel method and dip coating.This experiment used the raw material of tin (II) chloride hydrate (SnCl2.2H2O) as precursors and ammoniumfluoride (NH4F) as doping. The results showed that the processing time between the mixing of precursors anddoping was not so affect the stability of the solution. The significant factor affecting was the concentrationratio of the dopant/precursor and the conditions of mixing between the precursors and doping. Theconcentration ratio of the dopant/precursors of 10% produced the most stable conductive solution(US-1-½-½) with a thin layer of FTO has generated more regular hexagonal morphology, uniform and phaseof Sn4OF6.